2003
DOI: 10.1080/00071660310001616183
|View full text |Cite
|
Sign up to set email alerts
|

Microbial cross-contamination by airborne dispersion and contagion during defeathering of poultry

Abstract: 1. A readily identifiable strain of Escherichia coli K12 was used as a 'marker' organism to determine the sources, routes and patterns of microbial cross-contamination during mechanical defeathering of broiler chicken carcases. 2. Inoculation of scald water with the marker organism led to a relatively even pattern of carcase contamination during subsequent defeathering. Microbial cross-contamination was greater by this route of inoculation than by either surface inoculation of a 'seeder' carcase or oral inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…During slaughter mechanical evisceration often leads to intestinal rupture or leakage, followed by discharge of gut contents. Subsequently direct contact between carcases and contact of carcases with contaminated equipment surfaces can lead to horizontal transmission of faecal bacteria (Berndtson et al, 1996;Ono and Yamamoto, 1999;Berrang et al, 2001;Allen et al, 2003;Olsen et al, 2003). Our investigation showed that 8 out of 10 (80%) equipment samples were Campylobacter-positive (Table 3).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…During slaughter mechanical evisceration often leads to intestinal rupture or leakage, followed by discharge of gut contents. Subsequently direct contact between carcases and contact of carcases with contaminated equipment surfaces can lead to horizontal transmission of faecal bacteria (Berndtson et al, 1996;Ono and Yamamoto, 1999;Berrang et al, 2001;Allen et al, 2003;Olsen et al, 2003). Our investigation showed that 8 out of 10 (80%) equipment samples were Campylobacter-positive (Table 3).…”
Section: Discussionmentioning
confidence: 68%
“…Our findings agree with those reported by Rhakio and Korkeala (1997) who concluded that airborne bacteria play an important role in carcase contamination. Allen et al (2003) also implied that the major route of cross-contamination is by airborne dissemination and that direct contamination with the components of the machine played a minor role. By taking into consideration the low infective dose of Campylobacter spp., of about 500 cells (Black et al, 1988), these appreciable concentrations of airborne bacteria have relevance for product safety as well as for the workers' health.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, analogies can be drawn from the survival patterns of these organisms in other aerosols environments such as processing plants or hatcheries. E. coli K-12 was able to survive in aerosols or large droplet particulates during defeathering of poultry (2). The levels of E. coli in processing plant air have been reported to range from log 10 1.18 to 1.67 CFU/15 cubic feet (defeathering areas) (45).…”
Section: Discussionmentioning
confidence: 99%
“…In animal production facilities, air often contains high concentrations of particulate matter (PM; organic and/or inorganic particles) and airborne microorganisms and other biologically active substances that are also known as bioaerosols (Thedell et al, 1980;Clark et al, 1983;Heber et al, 1988a, b;Donham, 1990;Maghirang et al, 1997;Donham and Comro, 1999;Bilic et al, 2000;Chang et al, 2001;Predicala et al, 2001;Allen et al, 2003;Ko et al, 2008Ko et al, , 2010. The main sources of bioaerosols are animal skin, feed, bedding materials, and fecal materials.…”
Section: Introductionmentioning
confidence: 96%